2012
DOI: 10.1371/journal.pone.0051001
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota Is Essential for the Generation of Black Tea Theaflavins-Derived Metabolites

Abstract: BackgroundTheaflavins including theaflavin (TF), theaflavin-3-gallate (TF3G), theaflavin-3′-gallate (TF3′G), and theaflavin-3,3′-digallate (TFDG), are the most important bioactive polyphenols in black tea. Because of their poor systemic bioavailability, it is still unclear how these compounds can exert their biological functions. The objective of this study is to identify the microbial metabolites of theaflavins in mice and in humans.Methods and FindingsIn the present study, we gavaged specific pathogen free (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 47 publications
4
59
0
2
Order By: Relevance
“…For example, green tea catechins could be biotransformed by gut microbiota to ring-fission metabolites in in vitro models (24). Studies in our group also found that theaflavins, the major polyphenols in black tea, could be metabolized to gallic acid and pyrogallol by gut microbiota (18). In this study, we identified DH-2c, CA, and DH-CA as the metabolites of 2c by the human microbiota.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…For example, green tea catechins could be biotransformed by gut microbiota to ring-fission metabolites in in vitro models (24). Studies in our group also found that theaflavins, the major polyphenols in black tea, could be metabolized to gallic acid and pyrogallol by gut microbiota (18). In this study, we identified DH-2c, CA, and DH-CA as the metabolites of 2c by the human microbiota.…”
Section: Discussionmentioning
confidence: 51%
“…Interindividual differences in the composition of gut microbiota has become apparent, which may lead to variations in bioavailability and bioefficacy of dietary compounds, and eventually contribute to personalized nutrition approaches (18,22,25,26). Our present study shows that 2c is almost completely converted to DH-2c, CA, and DH-CA by subject B, but hardly metabolized by subject D within 120-h incubation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…25 In this study, we reported that methanolic extract of Bangladeshi black tea showed significant antibacterial activities against a range of pathogenic bacteria. Our results demonstrated that only one hour of incubation with black tea extract caused drastic reduction in bacterial cell number.…”
Section: Discussionmentioning
confidence: 94%
“…6 months) increased microbial diversity and had anti-obesity effects later on in the life of offspring [154]. L. plantarum 299v, L. plantarum DSM 15313 and other probiotics are currently being investigated for their ability to enhance the absorption of active polyphenolic chemicals that would be of relevance to brain health [155,156]. It is not our desire to belabor the point concerning the interaction between food and microbes; however, there are countless other components of traditional diets that could be singled out for relevancy.…”
Section: Introductionmentioning
confidence: 99%